2013
DOI: 10.1186/1471-2377-13-23
|View full text |Cite
|
Sign up to set email alerts
|

Performance measures for in-hospital care of acute ischemic stroke in public hospitals in Chile

Abstract: BackgroundThe aim of this study were to describe acute care of ischemic stroke patients and adherence to performance measures, as well as the outcomes of these events, in a sample of patients treated in public hospitals in Chile.MethodsWe retrospectively reviewed the medical charts of patients with ischemic stroke from a sample of seven public hospitals in the Metropolitan Region of Santiago. We analyzed adherence to the following evidence-based measures: clinical evaluation at admission, use of intravenous th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
(49 reference statements)
0
32
0
1
Order By: Relevance
“…2). There was one retrospective review [33]. Europe [26-28, 31, 32, 34] hosted 50% of studies, United States 25% [29,35,36] and the remainder were in Chile [33], Japan [37] and Canada [30].…”
Section: Resultsmentioning
confidence: 99%
“…2). There was one retrospective review [33]. Europe [26-28, 31, 32, 34] hosted 50% of studies, United States 25% [29,35,36] and the remainder were in Chile [33], Japan [37] and Canada [30].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, several studies reported wide confidence intervals and no statistically significant association between the reported KPIs and stroke case fatality; stroke unit admission (24), swallow/nutritional assessment (25,28,35), antiplatelets for ischemic stroke (23,28), anticoagulants for ischemic stroke, lipid management (28), DVT prophylaxis (28) and blood pressure lowering therapy (23). Surprisingly, in one study (17) the CT/MRI brain imaging was associated with increased risk of early case fatality (RR:…”
Section: Key Performance Indicatorsmentioning
confidence: 86%
“…Significant associations within single studies were observed for thrombolysis (19), early medical assessment (24), OT assessment (17), and antidepressant therapy (20), but there 28 was no evidence for the association between stroke case fatality and hyperthermia management (28), and neurological assessment (35).…”
Section: [Insert Figure 2 Here]mentioning
confidence: 99%
“…Hoffmeister et al (6) found 23.6% patients with pneumonia. Bruening and Al-Khaled (29) obtained 22.7%, while Gumbinger et al (27) registered 8% of patients with hospital-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter the time window between onset of stroke symptoms and drug infusion, greater the chances of a good prognosis. (6) The main clinical outcomes associated with this treatment are: significantly improved National Institute of Health Stroke Scale NIHSS score, hospital discharge, low occurrence of symptomatic hemorrhagic transformation, and low treatment-related deaths. (7,8) In Brazil, intravenous thrombolysis for ischemic stroke is conducted in several hospitals.…”
Section: Introductionmentioning
confidence: 99%